Hubungan Antara Akses Keuangan dan Pertumbuhan UMKM Dengan Literasi Keuangan Sebagai Variabel Moderator (Studi Kasus Pada UMKM Kuliner di Kota Malang) - Prameswari, Gita Anggun; Diana, Nur; Rudiningtyas, Dyah Arini (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The purpose of this study is to examine, using financial literacy as a moderator variable, the relationship between financial access and the growth of MSME (Micro, Small and Medium Enterprises). This research is quantitative research with a correlational approach using primary data obtained from questionnaires and measured using SPSS. The population in this research is culinary MSMEs in Malang City. Data was collected from 100 respondents through a questionnaire given to MSMEs in Malang City, using a purposive sampling technique. According to the analysis's findings, financial literacy significantly boosts MSMEs' growth while financial access significantly inhibits it. Financial literacy also acts as a buffer against the impact of financial access on MSMEs' growth.Keywords: Financial access, MSME growth, financial literacy